The Legal Definition of Railway Areas in Poland. The Limitations of Investment and Conducting Business Activity on the Railway Areas - Szulc, Piotr (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The paper analyses the legal definition of railway areas in Poland based on the Railway Transport Act. The author tries to find an answer to the question of what the legal status of railway areas in the Polish legal system is, with emphasis on the classification of railway areas to the wider group of special areas. Moreover, the paper describes the restrictions on investments on railway areas which are presented based on the previous judicature of the Polish administrative courts. Then other detailed obligations resulting from the special legal regime in this area are explained.